Ritual Perang Topat Sebagai Strategi Komunikasi Dalam Menjaga Kebhinekaan : Lessons Learnt dari Tradisi Suku Sasak dan Bali Di Pulau Lombok - I Wayan Suadnya; Eka Putri Paramita (Universitas Mataram, 2018)
Indonesia is pluralist a country with multi ethnics, cultures and religions. Religion is believed to provide guidance’s for humans life, however in other occasion it could become source of conflict. This happened due to monolithic belief which provides no space to accept the truth of other religions and cultures. This paper presents the meaning of ritual Perang Topat and lessons learned from the tradition of Sasak tribe who are Muslims and ethnic Bali who are Hindus.Perang Topat could be meaningful lessons learned in developing tolerance amongst different ethnics, culture and religions. It demonstrates that the Sasak ethnic and Balinese ethnic are able to live together in harmony both in daily lives and ritual ceremonies. Open communication and mutual understanding amongst ethnics is the key to sustain defferences. Therefore every one within the community do not provoc ofensive behaviour to other. Dialogue to find win win solutions is suggested as it it is demonstrated in the ritual. Thus this ritual need to be delivered so that it become lesson learnt in protecting unity. Values of the ritual should be explored and deseminated so that community understand and implement them. Key words: perang topat, lesson learnt, unity and differences